Maternal Prenatal Thyroid Function and Offspring ADHD: Findings from the ALSPAC Cohort - Fetene, D.; Betts, K.; Alati, Rosa (Lippincott Williams & Wilkins, 2018)
© Wolters Kluwer Health, Inc. All rights reserved. Thyroid hormone plays a pivotal role in the developing brain and may affect the development of attention deficit hyperactivity disorder (ADHD). This study aimed to examine the role of maternal thyroid function during pregnancy on offspring ADHD. A total of 2912 mother-child pairs were included from the Avon Longitudinal Study of Parents and Children. Thyroid parameters were assessed during the first trimester of pregnancy. Offspring ADHD was assessed using the Development and Well-Being Assessment at the ages of 7.5 and 15 years. The odds of presenting with ADHD were estimated using generalized estimating equations. Levels of thyroid-stimulating hormone (odds ratio [OR], 0.92; 95% confidence interval [CI], 0.48-1.75), free thyroxine (OR, 1.07; 95% CI, 0.87-1.32), and thyroid peroxidase antibodies (OR, 1.00; 95% CI, 0.80-1.25) were not associated with ADHD in children aged 7.5 and 15 years. This study showed no association between maternal thyroid function and offspring ADHD.